High-performance UWB Vivaldi antenna on FR4: A cost-effective solution for wearable technologies - Sahar Saleh; Tale Saeidi; Nick Timmons; Bader Alali; Faroq Razzaz; Ayman A. Althuwayb (Results in Engineering)
This paper introduces a novel Vivaldi Tapered Slot Antenna (VTSA) designed for wearable Ultra-Wideband (UWB) applications, utilizing a cost-effective FR4 substrate with a thickness of 0.8 mm. The proposed design achieves an 18.81 % size reduction (38.3 mm × 27.06 mm × 0.8 mm), a 36.16 % bandwidth (BW) increase, and a 16.63 % gain improvement compared to a VTSA using a Rogers RO4003C substrate (42.9 mm × 28.28 mm × 0.813 mm). The key contributions of this work include the effective use of the affordable FR4 substrate to achieve high performance, improvements in antenna compactness and BW through innovative slot designs, and the enhancement of gain and radiation pattern stability through the addition of directors to the slots. These modifications significantly boost the antenna's performance while maintaining a compact design. The antenna's suitability for wearable applications was validated through testing on flat and curved human phantoms made of skin, fat, and muscle, showing low Specific Absorption Rate (SAR) values across the UWB spectrum, confirming its safety for body-centric use. Measured results include S11 values below -10.56 dB over the 3.66–20.42 GHz range, a peak gain of 8.1 dBi, stable radiation patterns, and an average group delay of 0.83 ns. Simulations using Computer Simulation Technology (CST) were validated by experimental testing, demonstrating the antenna's potential for wearable and body-centric applications.